Search for anomalous top-quark couplings with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
Anomalous Wtb couplings modify the angular correlations of the top-quark decay products and change the single top-quark production cross section. We present limits on anomalous top-quark couplings by combining information from W boson helicity measurements in top-quark decays and anomalous coupling searches in the single top-quark final state. We set limits on right-handed vector couplings as well as left-handed and right-handed tensor couplings based on about 1fb-1 of data collected by the D0 experiment. © 2009 The American Physical Society.